2015
DOI: 10.1002/ajmg.a.37079
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency ofANO6, NELL2andDBX2in a boy with intellectual disability and growth delay

Abstract: We report on a 10-year-old-boy presenting with moderate intellectual disability (ID), impaired motor skills, hypotonia, growth delay, minor anomalies, misaligned teeth, pectus excavatum, small hands and feet, widely spaced nipples, and a 1.13 Mb de novo deletion on HSA12q12 (chr12:44,830,147-45,964,945 bp, hg19), deleting ANO6, NELL2, and DBX2 and the pseudogenes PLEKHA8P1 and RACGAP1P. We suggest DBX2 and NELL2 as disease-causing genes and their haploinsufficiency to be involved in the psychomotor delay in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 28 publications
1
30
3
Order By: Relevance
“…The deleted region in our patient partially overlaps with previously described deletions in 5 independent cases ( Fig. 2 ) [Tonoki et al, 1998;Miyake et al, 2004;Failla et al, 2008;Carlsen et al, 2015;Weng et al, 2018]. Four cases, including our patient, presented with psychomotor developmental delay, short stature, decreased head circumferences, as well as large low-set ears, strabismus, broad nasal bridges and/or noses, long philtrums, downturned corners of the mouth, and widely spaced nipples ( Table 1 ).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The deleted region in our patient partially overlaps with previously described deletions in 5 independent cases ( Fig. 2 ) [Tonoki et al, 1998;Miyake et al, 2004;Failla et al, 2008;Carlsen et al, 2015;Weng et al, 2018]. Four cases, including our patient, presented with psychomotor developmental delay, short stature, decreased head circumferences, as well as large low-set ears, strabismus, broad nasal bridges and/or noses, long philtrums, downturned corners of the mouth, and widely spaced nipples ( Table 1 ).…”
Section: Discussionsupporting
confidence: 83%
“…Four cases, including our patient, presented with psychomotor developmental delay, short stature, decreased head circumferences, as well as large low-set ears, strabismus, broad nasal bridges and/or noses, long philtrums, downturned corners of the mouth, and widely spaced nipples ( Table 1 ). The patient described by Carlsen et al [2015] showed most of the above-mentioned clinical features, although he had small ears, a wide mouth and rather an increased head circumference. At a clinical investigation at age 10 years, his height and weight were within the normal range (10th centile).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…These findings suggest that NELL2 and either TWF1 or TMEM117 play roles in development. NELL2 mRNA levels were also found to be decreased in patient 2 (Carlsen et al., 2015). Certain genes in 12q12 have the same development‐related functions.…”
Section: Discussionmentioning
confidence: 99%